Fabrication and Characterization of Electrospun Silk Fibroin/Gelatin Scaffolds Crosslinked With Glutaraldehyde Vapor - Mohammadzadehmoghadam, Soheila; Dong, Yu (Frontiers in Materials, 2019)
Bombyx mori silk fibroin (SF) /gelatin nanofibre mats with different blend ratios of 100/0, 90/10 and 70/30 were prepared by electrospinning and crosslinked with glutaraldehyde (GTA) vapour at room temperature. GTA was shown to induce the conformational transition of SFs from random coils to β-sheets along with increasing nanofibre diameters with the addition of gelatin into SFs. It was found that by increasing the gelatin content, crosslinking degree was enhanced from 34% for pure SF nanofibre mats to 43% for SF/gelatin counterparts at the blend ratio of 70/30, which directly affected mechanical properties, porosity, and water uptake capacity (WUC) of prepared nanofibre mats. The addition of 10 and 30 wt% gelatin into SFs improved tensile strengths of SF/gelatin nanofibre mats by 10 and 27% along with significant increases in Young’s modulus by 1.1 and 1.3 times, respectively, as opposed to plain SF counterparts. However, both porosity and WUC were found to decrease from 62 and 405% for pristine SF nanofibre mats to 47% and 232% for SF/gelatin counterparts at the blend ratio of 70/30 accordingly. To further evaluate the combined effect of GTA crosslinking and gelatin content on biological response of SF/gelatin scaffolds, the proliferation assay using 3T3 mouse fibroblast was conducted. In comparison with pure SFs, cell proliferation rate was lower for SF/gelatin constructs, which declined when the gelatin content increased. These results indicated that the adverse effect of GTA crosslinking on cell response may be ascribed to imposed changes in morphology and physiochemical properties of SF/gelatin nanofibre mats. Although crosslinking could be used to improve mechanical properties of nanofibre mats, it reduced their capacity to support the cell activity. GTA optimisation is required to further modulate the physico-chemical properties of SF/gelatin nanofibre mats in order to obtain stable materials with favourable bioactive properties and promote cellular responses for tissue engineering applications.